Strategi Pemasaran Pembukaan Rekening Online dalam Meningkatkan Jumlah Nasabah pada Bank Syariah Indonesia KCP Gunung Tua - Husnul Khotimah Nasution; Khairina Tambunan (Regress: Journal of Economics & Management, 2025)
This study examines public perceptions of online account opening services at Islamic banks in Gunung Tua within the context of rapid digital transformation in the banking sector. The expansion of Islamic banking in the digital era presents both opportunities and challenges, particularly in attracting customers through technology-based financial services. The research addresses how Islamic banks implement marketing strategies to increase the number of customers using online account opening services and identifies the obstacles encountered in the implementation process. This study employed a descriptive qualitative approach, with data collected through documentation techniques. The findings indicate that online account opening through mobile banking applications provides significant benefits and convenience for both banks and customers, particularly through various online transaction features that support efficiency and accessibility. Islamic banks have also attempted to strengthen their marketing strategies by optimizing digital services and targeting the millennial generation as potential users. However, several inhibiting factors remain, including vulnerability to digital fraud and the requirement for smartphones with adequate specifications to access mobile banking applications. The study concludes that strengthening digital security systems and improving technological accessibility are essential for enhancing customer trust and expanding Islamic banking services in the digital era.